1983
DOI: 10.1172/jci111040
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on metabolism in men and women. Importance of regional adipose tissue distribution.

Abstract: A B S T R A C T The distribution of adipose tissue thickness, fat cell weight (FCW), and number (FCN) were studied in four regions in randomly selected middleaged men and women and in 930 obese individuals. Both the obese and the randomly selected men were found to have the largest adipose tissue thickness in the abdominal region. Women, however, showed a relative preponderance for the gluteal and femoral regions. FCW increased with expanding body fat up to a maximal size of -0.7-0.8 ,ug/cell in each region.Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
594
3
34

Year Published

1985
1985
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,307 publications
(661 citation statements)
references
References 26 publications
30
594
3
34
Order By: Relevance
“…Body mass index (BMI) was calculated as weight (kg)/[height (m)] 2 . The waist-to-hip ratio was calculated as waist circumference (cm)/hip circumference (cm) [41].…”
Section: Methodsmentioning
confidence: 99%
“…Body mass index (BMI) was calculated as weight (kg)/[height (m)] 2 . The waist-to-hip ratio was calculated as waist circumference (cm)/hip circumference (cm) [41].…”
Section: Methodsmentioning
confidence: 99%
“…Body weight and height were recorded with standard techniques. Waist and hip circumferences were measured as described [22] and WHR calculated. Lean body mass (LBM) was calculated from bioimpedance analysis (BIA-101, Akern, Florence, Italy) [23].…”
Section: Methodsmentioning
confidence: 99%
“…Compared with small adipocytes, large cells are more insulin-resistant and lipolytic, release more inflammatory cytokines and less adiponectin [24,28], and are more frequently found in people with obesity-related metabolic disorders [29,30]. Therefore, adipose tissue cell composition, expressed as the relative number of large adipose cells in a given fat depot, is an important determinant of the metabolic activity and response to environmental changes of that depot.…”
Section: Biological Differences Between Visceral and Subcutaneous Adimentioning
confidence: 99%
“…an increase in cell size [1,2]. Studies on adipose tissue cellularity have reported that adipocytes become severely insulin-resistant when filled with more than 1 μg of lipid per cell, and new adipocyte recruitment normally occurs when the lipid content of the cells reaches ∼0.7-0.8 μg/cell [29]. The new cell recruitment may be triggered by a progressively altered secretion of proteins and lipid metabolites from the enlarging adipocytes [24,28], which could act as signalling molecules on the precursor cells in the adipose tissue bed to initiate and regulate adipogenesis.…”
Section: Biological Differences Between Visceral and Subcutaneous Adimentioning
confidence: 99%